2014
DOI: 10.1074/jbc.m113.534651
|View full text |Cite
|
Sign up to set email alerts
|

Gene Model 129 (Gm129) Encodes a Novel Transcriptional Repressor That Modulates Circadian Gene Expression

Abstract: Background: Circadian gene expression in mammals is driven by rhythmic CLOCK⅐BMAL1 activities. Results: Gm129 binds to the CLOCK⅐BMAL1 complex on DNA and represses its transcriptional activator activity to regulate the circadian gene expression phase. Conclusion: Gm129 is a novel circadian clock modulator. Significance: The discovery of Gm129 reveals a new regulatory component of circadian gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 36 publications
5
52
0
Order By: Relevance
“…S2). The mouse ortholog of this gene, Gm129, has been recently identified as having a circadian pattern of expression in mice (28,29). Many of these genes display circadian expression patterns in peripheral tissues of the mouse, such as the liver, heart, and/or skeletal muscle, and in the brain, including the SCN and cerebellum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S2). The mouse ortholog of this gene, Gm129, has been recently identified as having a circadian pattern of expression in mice (28,29). Many of these genes display circadian expression patterns in peripheral tissues of the mouse, such as the liver, heart, and/or skeletal muscle, and in the brain, including the SCN and cerebellum.…”
Section: Resultsmentioning
confidence: 99%
“…Another example is C1ORF51 (also known as Gm129, CHRONO, and CIART). Annayev et al (29) recently found that this protein acts as a novel transcriptional repressor with highamplitude oscillations in the mouse liver that directly interacts with BMAL1 to repress CLOCK/BMAL1 function in this tissue. Here, we find that this transcript has the highest level of rhythmicity of any gene that we identified in human cortex, suggesting it may have a similar important circadian function in human brain.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitation of Nr1d1 and Dbp mRNA levels was performed with the primer sets as described (Annayev et al 2014). Each sample was analyzed in triplicate, and cycle thresholds of individual genes were first normalized to corresponding Gapdh mRNA expression values obtained with the primer set.…”
Section: Quantitative Real-time Pcr and Data Analysismentioning
confidence: 99%
“…Quantitation of ChIP was performed with the primer sets described previously (Annayev et al 2014). Each sample was analyzed in triplicate.…”
Section: Quantitative Real-time Pcr and Data Analysismentioning
confidence: 99%
“…S1g in the supplemental material). Moreover, we examined if the promoters of these genes are bound by core clock factors identified in different chromatin immunoprecipitation sequencing (ChIP-seq) studies performed with liver cells or macrophages (8,9,(62)(63)(64)(65)(66)(67). Strikingly, 225 of these genes have been determined to be bound by at least one core clock factor (Clock, Per1, Per2, Cry1, Cry2, Npas2, Bmal1, Nr1d1, Nr1d2, or Rora; 97.8%, 1.36-fold increase above background; P Ͻ 0.001) (see Fig.…”
Section: Identification Of Genes With Circadian Expression In Nih 3t3mentioning
confidence: 99%